Masalah Dan Cabaran Guru Tahfiz Dalam Pelaksanaan Pengajaran Tahfiz Model Ulul Albab Sekolah Menengah Di Kementerian Pelajaran Malaysia - Siti Khadizah Kaimin; Ahmad Yussuf; Mohd Yakub @ Zulkifli Mohd Yusoff (Universiti Sains Islam Malaysia, 2024)
PAPER PROCEEDINGS THE 7TH INTERNATIONAL CONFERENCE ON QURAN AS FOUNDATION OF CIVILIZATION (SWAT) 2021 “ISLAMIC AND NON-REVEALED KNOWLEDGE IN FACING THE GLOBAL CHALLENGES” 6th – 7th October 2021 / 29 – 30 Safar 1443H Faculty of Quranic and Sunnah Studies Universiti Sains Islam Malaysia